From Social Justice to Metaphor: The Whitening of Othello in the Russian Imagination - Natalia Khomenko (Multicultural Shakespeare, 2021)
Othello was the most often-staged Shakespeare play on early Soviet stages, to a large extent because of its ideological utility. Interpreted with close attention to racial conflict, this play came to symbolize, for Soviet theatres and audiences, the destructive racism of the West in contrast with Soviet egalitarianism. In the first decades of the twenty-first century, however, it is not unusual for Russian theatres to stage Othello as a white character, thus eliminating the theme of race from the productions. To make sense of the change in the Russian tradition of staging Othello, this article traces the interpretations and metatheatrical uses of this character from the early Soviet period to the present day. I argue that the Soviet tradition of staging Othello in blackface effectively prevented the use of the play for exploring the racial tensions within the Soviet Union itself, and gradually transformed the protagonist’s blackness into a generalized metaphor of oppression. As post-collapse Russia embraced whiteness as a category, Othello’s blackness became a prop that was entirely decoupled from race and made available for appropriation by ethnically Slavic actors and characters. The case of Russia demonstrates that staging Othello in blackface, even when the initial stated goals are those of racial equality, can serve a cultural fantasy of blackness as a versatile and disposable mask placed over a white face.